2009
DOI: 10.1183/09031936.50130408
|View full text |Cite
|
Sign up to set email alerts
|

Current status of research on osteoporosis in COPD: a systematic review

Abstract: Patients with chronic obstructive pulmonary disease (COPD) are at increased risk of osteoporosis. However, the prevalence, correlates and effectiveness of treatment of osteoporosis in COPD patients remain unclear.We performed a systematic review of the literature to answer three questions. 1) What is the prevalence of osteoporosis in COPD? 2) What are identified correlates of osteoporosis in COPD? 3) What are the effects of treatment of osteoporosis in COPD? A computerised literature search in MEDLINE/PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
4
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(247 citation statements)
references
References 67 publications
12
218
4
9
Order By: Relevance
“…However, the prevalence of osteoporosis in patients with a long-term smoking history, leading to COPD, has been reported as high as 69% depending on the clinical setting and methodology. 40 Patients often present with additional risk factors of osteoporosis such as the use of corticosteroids, as opposed to smokers with no COPD diagnosis. As severity of COPD progresses, the proportion of patients with osteoporosis increases.…”
Section: Smoking and Smoking Cessationmentioning
confidence: 99%
“…However, the prevalence of osteoporosis in patients with a long-term smoking history, leading to COPD, has been reported as high as 69% depending on the clinical setting and methodology. 40 Patients often present with additional risk factors of osteoporosis such as the use of corticosteroids, as opposed to smokers with no COPD diagnosis. As severity of COPD progresses, the proportion of patients with osteoporosis increases.…”
Section: Smoking and Smoking Cessationmentioning
confidence: 99%
“…The COPD patients with osteoporosis had lower FEV1 and BMI values than the patients without osteoporosis. 22 In a retrospective review on 234 male patients referred for osteoporosis, revealed that COPD was the leading cause of secondary osteoporosis. 23 In the current study, out of total number of COPD (n=50), 27 (54%) patients (18 males and 9 females) had osteopenia and 14 (28%) patients (10 males and 4 females) had osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Не-сколько исследований показало снижение мине-ральной костной плотности ткани вне зависимости от тяжести течения ХОБЛ [2,19,20,45]. Другое ис-следование выявило остеопороз у 75% пациентов с 4 стадией ХОБЛ.…”
Section: хобл и остеопорозunclassified
“…Другое ис-следование выявило остеопороз у 75% пациентов с 4 стадией ХОБЛ. Существует ряд доказательств, что остеопороз ассоциирован с увеличением ригид-ности стенки сосудов и повышением уровня IL-6, что предполагает его связь с риском формирования сердечно-сосудистой патологии, и, следователь-но, с системным воспалением [19]. По данным A. Wedzicha, Allister D.A.…”
Section: хобл и остеопорозunclassified